EKSPERIMEN TURBIN AIR VERY LOW HEAD DENGAN VARIASI JUMLAH SUDU DAN VARIASI DEBIT - Susatyo, Anjar; Putra, Mohammad Alexin; Subekti, Ridwan Arief; Sudibyo, Henny; Ritonga, Muhammad Fachry (UNIMAR AMNI Semarang, 2024)
The vortex turbine is a water turbine with a type of reaction turbine that can be used in waterways with very low head. The amount of output power produced by the generator in the MHP system will vary according to the input parameters used, one of which is water discharge. Therefore, this research was conducted to determine the output power produced by the generator with different water discharge parameters using artificial waterways in the vortex turbine power plant prototype. In this research, it tries to conduct a research study to optimise the power and efficiency of the vortex turbine flow reaction turbine by varying the blade width and discharge variations on the upper curved cross-section blade type vortex flow reaction turbine at 5 and 8 blades. This study uses independent variables in the form of water discharge of 2.5 l/s, 2.6 l/s, 2.7 l/s, 2.8 l/s, 2.9 l/s, 3.0 l/s using turbine runner blade 5 diameter 100 mm, blade 8 diameter 100 mm, blade 5 diameter 130 mm and blade 8 diameter 130 mm. This research uses experimental research methods. The test results state that the greatest efficiency is produced in the turbine 8 blades of small diameter (100 mm) with a water capacity of 3.0 1/s which is 22.26% with a loading of 5.3 Ncm, at a turbine rotation of 164.89 rpm and produces shaft power of 0.915 W.